Intersession reliability of thoracolumbar multisegmental motor responses - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2013)
Study design: Experimental design. Objective: To determine test-retest reliability across sessions of the thoracolumbar multisegmental motor responses (MMR) in the upper and lower limbs of healthy subjects. Test-retest reliability of MMR has not been established or examined in previous studies. Settings: Neuro Laboratory of the Texas Woman's University (School of Physical Therapy, Houston, TX, USA). Methods: The MMR of 15 healthy subjects were tested over two sessions. T11-12 vertebral segments were electrically stimulated using surface electrodes. MMR signals of the upper and lower limbs were recorded, using surface electrodes, from the upper extremity muscles (abductor pollicis brevis, flexor carpi radialis, biceps brachii, triceps brachii), and from the lower extremity muscles (vastus medialis obliqus, medial hamstring, soleus, tibialis anterior). The peak-to-peak maximum amplitude and deflection latency were the dependent parameters. Data from the first session was compared with a second session (on a different day), using interclass correlation coefficient (ICC), to evaluate the reliability across sessions. In addition, data from the right limbs were compared with the left limbs. Results: MMR of the right and left, upper and lower extremities were comparable between limbs in all subjects. Further, signals were highly correlated between days of testing (ICC = 0.58-0.99) and was not statistically different between the two sessions in the same subject. Conclusion: These results indicate that MMR studies could be useful for serial testing of patients with neurological disorders, such as spinal cord injuries and diseases.
Keywords: Multi-segment motor response; Reliability; Correlation; Spinal cord; Thoracic; SPINAL EXCITABILITY; LEG MUSCLES; REFLEX